Interatividade e produção discursiva no rádio e na televisão: a participação da audiência e a conformação da mensagem informativa - Maciel, Suely [UNESP]; Kneipp, Valquiria Aparecida Passos (My University, 2012)
The study investigates the constitution of the informational message in production processes in interactive media and television, from situations in which contents are conveyed performed by the audience. The work shows that the declared strategies employed by listeners and viewers actualize itself in a series of controls and discursive constraints resulting from the dynamics in the means of production and the relationship established between broadcaster/program and its audience. Moreover, it is clear that, despite attempts to produce an effect independent of viewer and listener regarding your participation and opinion, there is a direction and a restriction on the possibilities of expression rather than technical, operational, are of discursive order.

O estudo investiga a constituição da mensagem informativa nos processos de produção interativa nas mídias sonora e televisiva, a partir de situações em que conteúdos realizados pela audiência são veiculados. O trabalho mostra que as estratégias enunciativas empregadas pelos ouvintes e telespectadores efetivam-se sob uma série de controles e coerções discursivas decorrentes da própria dinâmica de produção nos meios e da relação que se estabelece entre emissora/programa e seu público. Além disso, percebe-se que, apesar das tentativas de produzir um efeito de independência do telespectador e do ouvinte em relação a sua participação e opinião, ocorre um direcionamento e um cerceamento relativo das possibilidades de expressão que, mais que técnico-operacionais, são de ordem discursiva.
Interactivity and discursive production on radio and television: audience participation and conformation of the informational message
Keywords: Interactivity; Discursive communication; Journalism; Radio; Television; Interatividade; Comunicação discursiva; Jornalismo; Rádio; Televisão